Gastric Aspirate Shake Test for Prediction of Hyaline Membrane Disease in Preterm Babies - Sah, Arvind; Hayes, Bruce; Adhikari, Neelam (Annapurna Journal of Health Sciences, 2023)
Introduction: Hyaline Membrane Disease (HMD) remains a major cause of neonatal death and morbidity in infants of less than 37 weeks gestation. HMD is an important cause of RDS in newborns. To evaluate whether the Gastric Aspirate Shake Test in Preterm babies can predict the likelihood of Hyaline Membrane Disease. Methods: The Shake Test for prediction of Hyaline Membrane Disease was evaluated in 81 preterm newborns at NICU and Nursery, Patan Hospital. Over 0.5 ml of gastric aspirate was obtained within 1 hour of birth and mixed with an equal amount of normal saline for 15 seconds; 1 ml of 95% alcohol was then added and the mixture was agitated for the next 15 seconds. Then after 15 minutes, the airliquid interface was examined for bubbles. Results: Among 81 neonates, 46 developed HMD. 56.8% (26/46) of neonates with negative shake test developed HMD which was statistically significant(p<0.05). The sensitivity, specificity, positive predictive value, and negative predictive value were 96.29%, 76.47%, 86.6%, and 92.8% respectively. Conclusion: The gastric aspirate shake test is a rapid, simple, and inexpensive procedure and useful in predicting HMD and facilitating early transfer to the neonatal intensive care unit.